Sex Dimorphic Responses of the Hypothalamus-Pituitary-Thyroid Axis to Energy Demands and Stress - Parra-Montes de Oca, Marco Antonio; Sotelo-Rivera, Israim; Gutiérrez-Mata, Angélica; Charli, Jean-Louis; Joseph-Bravo, Patricia (Frontiers in Endocrinology, 2021)
The hypothalamus-pituitary-thyroid-axis (HPT) is one of the main neuroendocrine axes that control energy expenditure. The activity of hypophysiotropic thyrotropin releasing hormone (TRH) neurons is modulated by nutritional status, energy demands and stress, all of which are sex dependent. Sex dimorphism has been associated with sex steroids whose concentration vary along the life-span, but also to sex chromosomes that define not only sexual characteristics but the expression of relevant genes. In this review we describe sex differences in basal HPT axis activity and in its response to stress and to metabolic challenges in experimental animals at different stages of development, as well as some of the limited information available on humans. Literature review was accomplished by searching in Pubmed under the following words: “sex dimorphic” or “sex differences” or “female” or “women” and “thyrotropin” or “thyroid hormones” or “deiodinases” and “energy homeostasis” or “stress”. The most representative articles were discussed, and to reduce the number of references, selected reviews were cited.